When STING Meets Viruses: Sensing, Trafficking and Response - Li, Zhaohe; Cai, Siqi; Sun, Yutong; Li, Li; Ding, Siyuan; Wang, Xin (Frontiers in Immunology, 2020)
To effectively defend against microbial pathogens, the host cells mount an antiviral innate immune response by producing interferons (IFNs) and hundreds of IFN-stimulated genes (ISGs). Upon recognition of cytoplasmic viral or bacterial DNAs and abnormal endogenous DNAs, the DNA sensor cGAS synthesizes the second messenger 2’,3’-cGAMP, which induces the conformational change and trafficking of STING (stimulator of interferon genes, encoded by TMEM173), and the downstream activation of NF-κB and IRF3. Therefore, STING plays a pivotal role in mediating host protection from various DNA based microbial pathogens. This review is dedicated to summarizing the key function of STING in innate immune responses to DNA viruses and how its activation, intracellular trafficking, and post-translational modifications (PTMs) are regulated by the host and microbial proteins.